Understanding game data work - Heikki Tyni; Olli Sotamaa; Taina Myöhänen (Big Data & Society)
The game industry's content production, maintenance of live games, and processes of acquiring production funding increasingly rely on various kinds of data and its rigorous analysis. These new needs and functions have generated emerging forms of work, such as those of the data analyst, data engineer, and data scientist. Through in-depth interviews with 20 Finnish game industry professionals and an analysis of game industry job advertisements, this paper examines the work and identity of game industry data workers. Drawing from scholarship focused on game production, game work, and data labour, this article argues that organisational practices surrounding data professionals reveal the centrality of high-level data work in game studios focused on live service games and that data work is now performed not just by data analysts, but by the entire staff and management. As a precursor to the wider creative industries, we argue that creative work and data work in game companies are gradually converging, due to the datafied work environment facilitating datafied game work and the work of data professionals increasingly intertwining with creative tasks. Complicating the previous game studio hierarchy is the data analyst's dual role as both a subservient support function and a central broker of data. Adding nuance to this, the article argues that an important aspect of the work of bespoke data professionals in game companies is communication, in contrast to the high-level quantitative tasks often associated with analysis.